On the geometry spaces of hyperlane elemente with special metric - Mazėtis, Edmundas (Lietuvos matematikos rinkinys, 2008)
In this paper analysies metric space of hyperlane elemente with special metric. Is prowed, that the space Kartan–Landsbeg space is. Criteria of integrability of the intrinsic almost complex and almost product structures is found.